2022
DOI: 10.3390/ijms232315021
|View full text |Cite
|
Sign up to set email alerts
|

SecA2 Associates with Translating Ribosomes and Contributes to the Secretion of Potent IFN-β Inducing RNAs

Abstract: Protein secretion plays a central role in modulating interactions of the human pathogen Listeria monocytogenes with its environment. Recently, secretion of RNA has emerged as an important strategy used by the pathogen to manipulate the host cell response to its advantage. In general, the Sec-dependent translocation pathway is a major route for protein secretion in L. monocytogenes, but mechanistic insights into the secretion of RNA by these pathways are lacking. Apart from the classical SecA1 secretion pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The second option for a Gram-positive vector at least, like L. monocytogenes, is that Eno or Zea could perhaps be programmed to bind and thus enable secretion of custom RNA molecules like the Craspase gRNA [74,75].…”
Section: Overcomementioning
confidence: 99%
“…The second option for a Gram-positive vector at least, like L. monocytogenes, is that Eno or Zea could perhaps be programmed to bind and thus enable secretion of custom RNA molecules like the Craspase gRNA [74,75].…”
Section: Overcomementioning
confidence: 99%
“…While originally characterized for their ability to interfere with viral replication, type I interferons are increasingly recognized as important contributors in host-pathogen interactions involving intracellular bacteria. Studies in Francisella tularensis [1][2][3][4], Salmonella enterica serovar Typhimurium [5][6][7], Listeria monocytogenes [8,9] and Mycobacterium tuberculosis [10,11] have shown that these bacteria can specifically induce host type I interferons and that induction of this signaling pathway can directly impact host:bacteria interactions in vivo. For example, multiple studies have demonstrated that patients with active tuberculosis disease have blood transcriptomic signatures dominated by an upregulation of type I interferon inducible genes, including interferon-β (IFN-β).…”
Section: Introductionmentioning
confidence: 99%
“…While originally characterized for their ability to interfere with viral replication, type I interferons are increasingly recognized as important contributors in host-pathogen interactions involving intracellular bacteria. Studies in Francisella tularensis (1)(2)(3)(4), Salmonella enterica serovar Typhimurium (5)(6)(7), Listeria monocytogenes (8,9) and Mycobacterium tuberculosis (10,11) have shown that these bacteria can specifically induce host type I interferons and that induction of this signaling pathway can directly impact host:bacteria interactions in vivo. For example, multiple studies have demonstrated that patients with active tuberculosis disease have blood transcriptomic signatures dominated by an upregulation of type I interferon inducible genes, including interferon-ꞵ (IFN-ꞵ).…”
Section: Introductionmentioning
confidence: 99%